Learning by Doing Methods in the Field of Horticultural Skills to Improve the Calculating Ability of Students with Intellectual Disability - I Gusti Ayu Widia Anggun Swandewi; Endro Wahyuno; Sopingi Sopingi (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2019)
This study aims to describe the effect of Learning by Doing methods in the field of horticultural skills to improve the ability of calculating summation for students with intellectual disability. The experimental research method is used with the design of the one group pretest-posttest. The data were analyzed with the Wilcoxon of the Signed Rank Test. The results showed that the Learning by Doing method in the field of horticultural skills had an effect on the increase in the ability of calculating summation for students with intellectual disability.